2012
DOI: 10.1002/pssb.201200367
|View full text |Cite
|
Sign up to set email alerts
|

On the epitaxy of germanium telluride thin films on silicon substrates

Abstract: The growth by molecular beam epitaxy of GeTe thin films on highly lattice‐mismatched Si(111) substrates is reported. In situ reflection high‐energy electron diffraction and quadrupole mass spectrometry were employed to monitor the growth process in real time and tune the deposition conditions. Epitaxy was achieved in a window of substrate temperatures between 220 and 270 °C, using a Ge/Te flux ratio of ∼0.4. Extensive ex situ X‐ray diffraction characterization showed that the epitaxial layers crystallize in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 39 publications
2
38
0
1
Order By: Relevance
“…In fact, whereas ferroelectric displacements have been clearly observed with many experimental techniques, 20 GeTe shows a high tendency to form Ge vacancies. 21,22 This in turn leads to a p-degenerate semiconducting behavior, calling into question the possibility to switch the ferroelectric state in such a "conducting material", therefore hindering the control of spintexture via an electric field (it is worth noticing that FE switching has been, however, recently reported in epitaxial GeTe films). 23 The search for new FERSC materials is hence essential to achieve better properties and performances.…”
Section: 15mentioning
confidence: 99%
“…In fact, whereas ferroelectric displacements have been clearly observed with many experimental techniques, 20 GeTe shows a high tendency to form Ge vacancies. 21,22 This in turn leads to a p-degenerate semiconducting behavior, calling into question the possibility to switch the ferroelectric state in such a "conducting material", therefore hindering the control of spintexture via an electric field (it is worth noticing that FE switching has been, however, recently reported in epitaxial GeTe films). 23 The search for new FERSC materials is hence essential to achieve better properties and performances.…”
Section: 15mentioning
confidence: 99%
“…Experimental details regarding the growth procedure and structural characterization can be found elsewhere. 17 The ferroelectric switching behavior of the GeTe films has been studied using PFM local spectroscopy and imaging modes. 18 DFT-based computer simulations have been performed to investigate the possible structural changes associated with polarization reversal.…”
mentioning
confidence: 99%
“…This is in good agreement with the bulk lattice constant of 10.666 A and previous results grown on normal Si(111) substrates. [15] From the thickness fringes surrounding the a-GeTe(00.3) peak, Figure 1(b), a thickness of 32 nm is determined. Based on the HRXRD data, it is concluded that the crystalline GeTe layer grown on the Si(111) membrane has a fairly good structural quality.…”
Section: Resultsmentioning
confidence: 99%
“…More details about the growth conditions can be found elsewhere. [15,16] The samples were capped with Si x N y by in situ radio-frequency magnetron sputtering.…”
Section: Methodsmentioning
confidence: 99%